Combined associations of social determinants of health and cardiovascular health with all-cause and cause-specific mortality. - Boxuan Pu (19987285) (2025)
Participants were classified into six groups according to the combined categories of unfavorable SDoH (low and high burden) and CVH (low, moderate, and high). Multivariate models were adjusted for age, sex, race/ethnicity, cardiovascular disease history, and cancer history. Abbreviations: SDoH: social determinants of health; CVH: cardiovascular health; HR: hazard ratio; CI: confidence interval; CVD: cardiovascular diseases.